The wide world of coding : the people and careers behind the programs - Connor-Smith, Jennifer, 1972- (Twenty-First Century Books, 2020)
Discusses the careers of software development and computer coding, how to enter the fields, and how the industry is changing. Concludes with a timeline and an index.